Aluminium and Durability: Reviewed by Inspection and Testing. (2015) - Stacey, Michael; Bayliss, Chris
Abstract: The durability of aluminium used in architecture is reviewed by inspection and testing. A global survey of aluminium in architecture and infrastructure over the past 120 years identified aluminium pioneers, from the earliest known example in 1895 within the Church of St Edmund, England to the Hongkong Bank, 1985. This forged the research question: "are there aluminium based projects that are fit and forgotten; functioning well for the owners and users, whilst out-performing the contract guarantees provided when they were assembled?" Thus twelve case studies were researched and inspected from which three projects underwent non-destructive testing of the aluminium finishes.